Environmental instability in heterogeneous domains - Maini, P; Benson, D; Sherratt, J (1992)
Species interaction models have been widely studied to investigate the phenomena of population fluctuations and extinction. To a great degree, these models have assumed that the environment is spatially homogeneous, although discrete 'patch models' suggested that movement between patches has important global implications. However, in continuous models the effect of inhomogeneities in the habitat has received relatively little attention, although the threat posed to nature reserves by partly disrupting the habitats of competing species has been studied.